2021
DOI: 10.1111/cas.14767
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐FIRΔexon2 autoantibody as a novel indicator for better overall survival in gastric cancer

Abstract: There is no clinically available biomarker for efficiently indicating the overall survival or therapy response of gastric cancer (GC). The autoantibodies (Abs) in the sera of anti‐far‐upstream element‐binding protein‐interacting repressor‐lacking exon2 (FIRΔexon2), anti‐sorting nexin 15, and anti‐spermatogenesis and oogenesis–specific basic helix–loop–helix 1 were markedly higher in GC patients than in healthy donors (HDs). These Abs were identified by large‐scale serological identification of antigens by reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…In our previous study, a high level of anti‐FIRΔexon2 Abs in the sera of patients with GC indicated better overall survival (OS) 45 . In contrast, in patients with CRC was not significant (Figure S2).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our previous study, a high level of anti‐FIRΔexon2 Abs in the sera of patients with GC indicated better overall survival (OS) 45 . In contrast, in patients with CRC was not significant (Figure S2).…”
Section: Discussionmentioning
confidence: 83%
“…In our previous study, a high level of anti‐FIRΔexon2 Abs in the sera of patients with GC indicated better overall survival (OS). 45 In contrast, in patients with CRC was not significant (Figure S2 ). The fact that CEA and CA19‐9 negative patients had better survival rates suggests the reliability of this data analysis.…”
Section: Discussionmentioning
confidence: 90%
“…Serological antigen identification by cDNA expression cloning (SEREX) is a liquid biopsy method and an effective technique for screening antigen and antibody markers ( 19 , 20 ). SEREX screens antigens related to tumors and autoimmune diseases including GI cancers [EC ( 21 , 22 ), GC ( 23 ), LC ( 24 ), and CRC ( 25 ) and PC ( 26 )], multiple sclerosis (MS) ( 27 ), systemic sclerosis (SSc) ( 28 ), systemic lupus erythematosus (SLE) ( 29 ), rheumatoid arthritis (RA) ( 30 ), and others. In earlier studies, we successfully applied SEREX to AS-related diseases and identified antibodies against CPSF2, DIDO1, FOXJ2, MMP1, CBX1, CBX5, and LAMP1 in TIA and CI ( 31 33 ).…”
Section: Introductionmentioning
confidence: 99%